(untitled) (Research, Society and Development, 2021)
This reflection presents the ethical sense of suffering in the medical, patient and student relationship, based on a phenomenological approach to Levinas’s ethics. Some contemporary challenges are presented in the doctor and patient relationship. The main challenge of the doctor is to face the suffering of the other by the ethical sensibility, placing the patient as the center in which he plans his treatment. However, the patient is also invited to be part of the treatment and in some way taking also responsibility for illness, as a way of helping to get out of passivity and make recovery more effective. Another challenge is the doctor dealing with patients who are informed by virtual nets, as if there were a banalization of medical knowledge, since "everyone knows about medicine". However, beyond this misunderstanding, there is a recognition of the patient’s knowledge that can also contribute to a new narrative of his illness along with medical listening.